Pengetahuan dan praktik masyarakat Indonesia dalam menghadapi pandemi Covid-19 - Andi Eka Yunianto; Taufiq Firdaus Al-Ghifari Atmadja; Emy Yuliantini; Miratul Haya; Ahmad Faridi; Suryana Suryana (Politeknik Kesehatan Kemenkes Aceh, 2020)
Background: Increasing cases of COVID-19 in Indonesia every day and creating new clusters. One of the reasons for the increase in cases is the level of knowledge about COVID-19. Knowledge is a person's foundation in practicing his activities every day. A good practice is based on a good level of knowledge.Objectives: The research objective is to see an overview of the knowledge and practices of Indonesian society in dealing with the COVID-19 outbreak.Methods: This study used a cross-sectional design with 6,557 respondents, the criteria were above 16 years old who live in Indonesia. The research was conducted in June 2020. The questionnaire is an e-survey using google form media and is distributed via social media (Whatsapp, Facebook, and Instagram). The knowledge and practice of the people in this statistical analysis used only univariate analysis.Results: The results show that in general the knowledge of the Indonesian people is correct from the 12 questions asked. The mean score of knowledge of male respondents was 75.13±29.47, while for women it was 77.16±26.50. The average practice score of male respondents was 81.33±19.95, while the female respondents were 87.18±16.13.Conclusion: The higher the knowledge, the better the community practices in preventing and reducing the transmission of the COVID-19 outbreak.